Perubahan Budaya Ibu Rumah Tangga Pasca Maraknya E-Commerce di Indonesia - Nanda Anderson; Azam Beshad; Fajar Muhammad Ravi (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This research discusses the activities of housewives in using E-Commerce, which have a positive impact. It is a process of changing the activities of housewives who used to shop for goods traditionally or conventionally to digital. The rapid development of technology is what ultimately led to the change in the activities of housewives, where they used to transact face-to-face with sellers and buyers, but now sellers and buyers only transact virtually or online using E-Commerce. This research uses a qualitative research method, where the researcher aims to describe and analyze the changes in the behavior of housewives related to E-Commerce activities from offline to all-online systems. Social change in housewives is not a result or product, but a process. This process of change is, of course, the result of an agreement or joint decision made by individuals or a community.